How do sporting organisations conceptualise and operationalise the prevention of violence against women? - Hamilton, Gemma (The Australian and New Zealand journal of criminology, 2020)
Sport settings have great potential to influence social change and are therefore important locations to engage in the prevention of violence against women. The following study draws on in-depth interviews with 16 stakeholders who have been involved with the implementation of prevention programmes within competitive/team sport settings. A qualitative thematic analysis of the interviews was undertaken to examine how sporting organisations understand, strategise and practise prevention work in Australia and New Zealand. Implications for long-term changes in the prevention of violence against women are discussed with reference to key prevention actions and frameworks.